Laponite-Based Nanocomposite Hydrogels for Drug Delivery Applications - Samuel T. Stealey; Akhilesh K. Gaharwar; Silviya Petrova Zustiak (MDPI AG, 2023)
Hydrogels are widely used for therapeutic delivery applications due to their biocompatibility, biodegradability, and ability to control release kinetics by tuning swelling and mechanical properties. However, their clinical utility is hampered by unfavorable pharmacokinetic properties, including high initial burst release and difficulty in achieving prolonged release, especially for small molecules (<500 Da). The incorporation of nanomaterials within hydrogels has emerged as viable option as a method to trap therapeutics within the hydrogel and sustain release kinetics. Specifically, two-dimensional nanosilicate particles offer a plethora of beneficial characteristics, including dually charged surfaces, degradability, and enhanced mechanical properties within hydrogels. The nanosilicate-hydrogel composite system offers benefits not obtainable by just one component, highlighting the need for detail characterization of these nanocomposite hydrogels. This review focuses on Laponite, a disc-shaped nanosilicate with diameter of 30 nm and thickness of 1 nm. The benefits of using Laponite within hydrogels are explored, as well as examples of Laponite-hydrogel composites currently being investigated for their ability to prolong the release of small molecules and macromolecules such as proteins. Future work will further characterize the interplay between nanosilicates, hydrogel polymer, and encapsulated therapeutics, and how each of these components affect release kinetics and mechanical properties.